If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8 = 23 + 3x Reorder the terms: 8 + 6x = 23 + 3x Solving 8 + 6x = 23 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + 6x + -3x = 23 + 3x + -3x Combine like terms: 6x + -3x = 3x 8 + 3x = 23 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + 3x = 23 + 0 8 + 3x = 23 Add '-8' to each side of the equation. 8 + -8 + 3x = 23 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = 23 + -8 3x = 23 + -8 Combine like terms: 23 + -8 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 9s^2-81=0 | | -5x-1=69 | | P=-.3x^2+80x-1500 | | 5n-5=70 | | 27.95+12x=12.95+32x | | 6x+8=32+3x | | 38=-4+6v | | 100n-300=450-50x | | k/9=12 | | -234=9(-8+v) | | 4x+4=3x+15 | | 10(3+a)=-30 | | 3w-9=3 | | 12x+4=14x | | 9=2b-3 | | t/5=11 | | 16-0.2x=9 | | 12n-2=12n | | -25=-(7+X) | | 5x^3-40x^2=0 | | 5x^2-9x+5=0 | | 3=1x+3 | | 14=-(V-3) | | 5x-3+2=2x-8+7x | | 3(4n-2n)=12n | | 5+5a=35 | | 10=4(v-2)-6v | | 17x+12=5x^2 | | -180=10n+10 | | 5x^2+15x-40=0 | | y=x^2+5x-2 | | 20x+25x=145 |